Visible Light Activation of Spin‐Silenced Fluorescence. Issue 47 (24th May 2018) - Eing, Matthias; Tuten, Bryan T.; Blinco, James P.; Barner‐Kowollik, Christopher
Abstract: A self‐reporting, profluorescent, visible light‐induced release system is introduced. Fluorescence activation is enabled by a mild remote trigger signal that can be monitored with the naked‐eye in real time. The light‐responsive spin‐silenced polymer is synthesized via an Ugi post‐polymerization modification incorporating paramagnetic nitroxides and a light cleavable fluorophore moiety. Abstract : Getting turned on by blue light : We pioneer a visible light‐induced self‐reporting release system, where the cleavage of the molecular cargo is induced by light and read out by a strong visible fluorescence switch‐on. The molecular construct exploits a multi‐component reaction to tether a nitroxide spin‐silenced fluorophore to a macromolecular delivery vector. The visible light‐induced molecular release event can be monitored with the naked eye.